Pengaruh Profitabilitas, Leverage, Liquidity, dan Capital Intensity Terhadap Tax Avoidance Dengan Ukuran Perusahaan Sebagai Variabel Moderasi (Studi Kasus Perusahaan Perbankan di Indonesia yang terdaftar di Bursa Efek Indonesia Pada Tahun 2016-2020) - Oktari, Natasha; Yantiana, Nella; Noviarty, Helisa (APSSAI ACCOUNTING REVIEW, 2024)
Research aims: This study aims to analyze the influence of Profitability, Leverage, Liquidity, and Capital Intensity on Tax Avoidance with Firm Size as a moderating variable. The object of this research is banking companies listed on the Indonesia Stock Exchange during the period 2016 to 2020. Design/Methodology/Approach: This study uses secondary data, and sampling is done using the purposive sampling method. From the entire set of companies, 34 companies were selected that met the criteria for testing. The collected data was then analyzed using regression techniques and moderated regression analysis (Islam et al., 2020), with the assistance of Eviews software for data processing. Research findings:  The results of the study show that profitability and liquidity have a significant influence on tax avoidance. Conversely, leverage and capital intensity do not have an influence on tax avoidance. Additionally, the results indicate that firm size can moderate the influence of profitability and leverage on tax avoidance. However, firm size cannot moderate the influence of liquidity and capital intensity. Theoretical contribution/Originality: This study provides an original contribution by examining the role of firm size as a moderating variable in the relationship between profitability, leverage, liquidity, capital intensity, and tax avoidance in the banking sector in Indonesia. Practitioner/Policy implication: The implications of this research are that it can be used by regulators and policymakers to understand the factors influencing tax avoidance in the banking sector. Banks can use these findings to optimize their financial strategies related to profitability and liquidity. Regulators can also consider firm size when designing tax policies for the banking sector